[OP.5A.01] CENTRAL BLOOD PRESSURE RELATES MORE STRONGLY TO RETINAL ARTERIOLAR NARROWING THAN BRACHIAL BLOOD PRESSURE. (September 2016) - Tabara, Y.; Kumagai, K.; Yoshimura, N.; Matsuda, F.
Abstract : Objective: Although central blood pressure (BP) is considered to be more closely associated with large arterial remodeling and cardiovascular outcomes than brachial BP, few studies have investigated these associations with changes in small arteries. As morphological changes in retinal vessels might be associated with cardiovascular outcomes, we conducted a cross-sectional study to investigate the association of central BP with retinal vessel caliber. Design and method: Study subjects consisted of 8, 054 apparently healthy middle-aged to elderly citizens (52 ± 13 years old) who were participants of the Nagahama Study. Basic clinical parameters, including plasma markers, were measured at baseline. Central BP was estimated by the radial arterial waveform by calibrating brachial BP. Central retinal arteriolar equivalent (CRAE) was computationally measured using fundus photography. Results: CRAE was decreased with age. Basic factors that were significantly associated with CRAE included age (r = −0.210, p < 0.001), habitual smoking (current smoker 128.7 ± 11.7, non-smoker 125.7 ± 11.9 μm, p < 0.001), and drinking (habitual drinker 125.2 ± 11.9, non-drinker 126.6 ± 11.9, μm, p < 0.001). CRAE was most strongly associated with central systolic BP (SBP) (r = −0.324, p < 0.001), followed by diastolic BP (r = −0.292, p < 0.001), and central pulse pressure (PP) (r = −0.226, p < 0.001). Results of Meng-Rosenthal-Rubin method analysis indicated that the correlation coefficient between BPs and CRAE was significantly larger in central BP than brachial BP (r = −0.300, p < 0.001). After adjustment for possible covariates, brachial SBP (β = −0.221, p < 0.001) and central SBP (β = −0.239, p < 0.001) were independently associated with CRAE. Further, higher brachial SBP (β = −0.226, p < 0.001) and smaller PP amplification (β = 0.092, p < 0.001) were identified as independent determinants of narrowing of CRAE in the same equation, which indicated the superiority of central BP. Central BP-determined hypertensive subjects (HT) had a significantly narrower CRAE independently of brachial BP (central/brachial: HT/HT 121.4 ± 11.5, HT/normotension (NT) 120.9 ± 11.2, NT/HT 125.1 ± 11.9, NT/NT 128.1 ± 11.5 μ). Conclusions: Central BP was more closely associated with the narrowing of CRAE than brachial BP. Slight increases in central BP might be involved in the morphological changes in small retinal arteries, even in subjects with optimal brachial BP.